ORIENTALIS DAN DUPLIKASI BAHASA ALQURAN (Telaah dan Sanggahan atas Karya Christoph Luxenberg) - Yusuf, Khaeruddin (State Institute of Islamic Studies (IAIN) Palu, 2012)
Abstract: The Qurâ€™an is a holy book seving as the source of inspiration for the seekers of science, including those who belong to orientalists. They make Alquran as an object of study and research among both academic and non-academic. One of the most contemporary issues of orientalist studies of the Qurâ€™an was written by Christoph Luxenberg â€œDie Syiro-aramaeische Lesart des Koran: Ein beitrag Zur Entschluesselung der Koranspracheâ€Â (The Syiro-Aramaic Reading of the Qurâ€™an: A contribution to the Language of the Qurâ€™an Description). Luxenberg says that the Qurâ€™an is heavily influenced by the Syriac-Aramaic language; therefore, to understand the Qur'an properly, one must learn it through the Syriac-Aramaic language. According to Luxenberg, the Syriac-Aramaic language was the language of Lingua Franca of Arabic society at the time of the Prophet, while the Arabic language (Fusha) came later after the Syriac-Aramaic language had reached perfection. This article tries to review the opinion of Luxenberg, then gives arguments by citing the opinion of some prominent Islamic reviewers.Kata Kunci: Orientalis, otentitasÂ Alquran, bahasa Alquran, Christoph Luxenberg